Addition/Substitution Approach of TsNHCH2SiMe2CH2Cl with Isocyanates or Isothiocyanates To Construct 1,3,5-Diazasilinan-2-ones or 1,3,5-Thiazasilinan-2-imines - Li, Yi; Hu, Tianbao; Gao, Lu; Song, Zhenlei (Synthesis, 2022)
TsNHCH2SiMe2CH2Cl has been exploited as a 1,4-dipole synthon for the synthesis of 1,3,5-diazasilinan-2-ones by a sequential N-addition/N-substitution process with isocyanates, or for the synthesis of 1,3,5-thiazasilinan-2-imines with isothiocyanates by a sequential N-addition/S-substitution process.
Keywords: silaazacycles; ‘carbon-silicon’ switching; 1,3,5-diazasilinan-2-one; 1,3,5-thiazasilinan-2-imine; cyclization